Oxidative Ammonolysis of Wheat Straw Lignosulphonate : a Source of Nitrogenous Fertilizew Soil Conditioner - Srivastava, Anita; Bhandari, K. S. (Indian Forester, 2001)
Sulphite pulping of wet cleaned wheat straw was carried out using 12% Na2 S03 at 160°C for 120 minutes maintaining 1:6 bath ratio. Sulphite spent liquor was collected by squeezing the cooked material. Lignosulphonate was isolated from sulphite spent liquor and subjected to oxidative ammonolysis at 90, 110, 130 and 150°C for 0, 30, 60 and 90 minutes reaction time after attaining the maximum temperature. Each ammonolysed product was analysed for its elemental composition. C/N ratio of each product was computed from these values. It was observed that amount of nitrogen in Lignosulphonate increased with the increase in reaction time and temperature, consequently, the C/N ratio ,.was decreased. However, reaction temperature has more pronounced effect on nitrogen incorporation rather than the reaction time. At 90°C reaction temperature, the improvement in nitrogen content with reaction time was consistent but at slow rate. At 110°C and 130° reaction temperature, nitrogen content was improved sharply up to 30 minute reaction time followed by marginal improvement beyond 30 minutes. It was improved to 3.95 ± 0.23%, 4.29 ± 0.21 % and 4.98 ± 0.04% for 30,60 and 90 minutes reaction time corresponding to 8.35 ± 0.57, 7.64 ± 0.47 and 6.53 ± 0.12 C/N ratio as against 0.00% and 1.82 ± 0.18% nitrogen content for control sample and sample ammonolysed for 0 minute which correspond to - 17.99 ± 2.34 C/N ratio. However, at 150° C reaction temperature, the nitrogen content was sharply increased to 6.98% in 60 minutes reaction time corresponding to C/N ratio 4.19 as against 0.00, 2.48 and 4.87% for control sample and samples ammonolysed for o and 30 minutes which correspond to 13.17 and 6.59 C/N ratio. Beyond 60 minutes, though it was improved to 7.57% corresponding to C/N ratio 3.74 but comparatively at slower rate. The carbon hydrogen and sulphur content were decreased and oxygen content was increased in the initial period of reaction, subsequently it had also shown the decreasing trend as reaction proceeds. Results are discussed in the paper at adequate length.